Developing a health surveillance strategy for professional footballers in compliance with UK health and safety legislation. Issue 2 (June 1997) - Fuller, Colin W; Hawkins, Richard D
Abstract : The need for health surveillance for professional footballers has been assessed against criteria specified in UK health and safety legislation. As footballers suffer from chronic injuries under normal playing conditions, professional football clubs have a requirement to implement health surveillance programmes to protect their players. A health surveillance programme, based on benchmarking a player's fitness and addressing the issues of pre-recruitment, pre-season, during-season, post-season, and rehabilitation assessment, is proposed.